Research of Curve Passing Performance of Track Car in Vehicle Group Chain Conveyor based on SIMPACK - Yang Li; Yaocheng Zhang; Zhaojian Yang; Xianglei Li (Jixie chuandong)
Abstract The vehicle group chain conveyor is the new kind of continuous material conveying equipment in bulk materials field. For its essential structure， which is the continuous track group car carrying the conveyor belt and relying on the rail runs. Curve passing performance at curve working conditions is studied. A nonlinear dynamics model of the conveyor track group passing the curve is established and analyzed. The multi-body dynamics simulation software SIMPACK is used to build the track group car model. Based on the different working conditions and the structure of the car， the variation of the curve passing performance of the track car is analyzed. The simulation results show that dynamics performance index of the track car in vehicle group chain conveyor under various working conditions decreases with the increase of the vehicle speed and spacing， and increases with the increase of the curve radius and transition curve length. Track car with smaller wheelbase and articulated body can adapt to curved track. The curve of the track car has good performance and all indicators are within the safe limit range.